Sexual dimorphism in the response to antidepressant therapy: Biological basis and clinical implications - Nedeljković, Jelena; Stanić, Dušanka; Petrović, Jelena; Ivanović, Ana; Ilić, Miloš; Nikolašević Stojković, Gorana; Pejušković, Bojana; Pešić, Vesna (Archives of Pharmacy, 2024)
Depression represents a complex mental health problem worldwide, affecting millions of people and causing significant societal and personal distress. A plethora of evidence has emerged indicating an important role of gender dimorphism in depression, with prevalence rates, symptomatology, and treatment responses differing between men and women. Women are generally more likely to suffer from depression, which is often attributed to hormonal influences, psychosocial stressors, and gender-specific coping mechanisms. In contrast, men may exhibit different depressive patterns, characterized by externalizing behaviors and higher suicide rates. Neurobiological studies highlight gender-specific differences in brain structure and function, as well as in neurotransmitter systems, which may impact treatment efficacy and response variability. While conventional pharmacotherapy remains pivotal, personalized approaches that integrate psychotherapeutic modalities such as cognitive-behavioral therapy and mindfulness-based interventions have increased in recent years. However, gender differences in treatment outcomes emphasize the need for differentiated, gender-sensitive clinical strategies. This review summarizes the current literature to highlight the complexity of depression and the importance of tailoring interventions to optimize clinical outcomes in diverse populations.
Keywords: depression; gender dimorphism; sex differences; antidepressants